Effect of ovulation on serum cholesterol in women of reproductive age group - Panigrahi, Madhuri; Panda, Santosh K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Reproduction and contraception is mostly central around ovulation. The sex hormones undergo changes in levels with ovulation. They also play an important role in cholesterol metabolism, especially oestrogen. Aim of our study was to find out changes in serum cholesterol before and after ovulation in women of reproductive age. Methods: In present study 70 women of reproductive age group (15-49years) were recruited. Serum cholesterol was measured around time of ovulation. Results: It was found that, during the follicular phase there was a significant increase in total cholesterol and LDL-C concentrations compared to post ovulatory phase. During the ovulatory phase there was a decrease in total cholesterol and increase in HDL-C compared to follicular phase. VLDL levels showed increasing trend from follicular to post ovulatory phase. Conclusions: Ovulation improves cardiovascular risk factors which may account of the decreased risk of cardiovascular diseases among ovulating women. And secondly, the menstrual cycle phase should be taken into account when evaluating cholesterol levels among reproductive age group women.